A bibliometric analysis of greenwashing research: a closer look at agriculture, food industry and food retail. Issue 13 (19th November 2021) - Montero-Navarro, Antonio; González-Torres, Thais; Rodríguez-Sánchez, José-Luis; Gallego-Losada, Rocio
Abstract : Purpose: This paper aims at providing an overview and synthesis of the existing body of knowledge about greenwashing. Special attention is paid to the articles directly linked with agriculture, food industry and food retail. Design/methodology/approach: A bibliometric analysis was performed over 351 documents extracted from the WoS database, using SciMAT and VOSviewer software programs. Findings: Three periods in the academic literature about greenwashing can be distinguished: ground-setting (2003–2010), trail-blazing (2011–2015) and remarkable growth (2016–2020). Along this evolution, a body of knowledge which stemmed from the literature about CSR has achieved a major development, deploying different research lines such as stakeholders' management, marketing and communication and audit. A specific analysis of the academic literature about greenwashing in agriculture, food industry and food retail has been carried out, showing a need for further development. Social implications: The development of scientific knowledge about greenwashing puts this social claim on the spotlight of business management studies, helping to fight greenwashing and, this way, to reduce the environmental impact of corporate activities. Studying greenwashing will help to reduce its frequency and, therefore, heal the planet. Originality/value: Some previous studies have provided systematic reviews of the literature using different approaches, but they did not untangle the intellectual structure and the evolution of the body of research about greenwashing. This article originally provides a thorough analysis of these aspects, as well as a closer look at the impact of greenwashing practices in the academic literature regarding agriculture, food industry and food retail.